PENGARUH TINGGI MUKA AIR TANAH PADA PERTUMBUHAN TANAMAN CABAI (Capsicum annum) DENGAN IRIGASI BAWAH PERMUKAAN (Subsurface irrigation) - Adrian Fajriansyah; Rahmad Hari Purnomo; Hilda Agustina (Jurnal Teknik Pertanian Sriwijaya, 2012)
The research objective was to determine the effect of soil water level differences, porosity and semi permeable layer thickness for subsurface irrigation on chilly (Capsicum annum) crop growth.  It used split plot design with two factors of treatment and three replications for each treatment factor.  The first factor was soil water level height consisting of 4 cm, 8 cm and 12 cm as a main plot.  The second factor was combination of thickness (t) and sand (s) as well as clay (c) composition as subplot consisting of A1B1 (1 cm, 30%, 70%), A1B2 (1 cm, 40%, 60%), A1B3 (1 cm, 50%, 50%), A2B1 (1,5 cm, 30%, 70%), A2B2 (1,5 cm, 40%, 60%), A2B3 (1,5 cm, 50%, 50%). The observed parameters were water content (%), climatic data, crop length increment (cm), leaves number, flower shoots number, fruits number and crop dry matter weight (g). The results showed that the highest crop grwoth was found on 8 cm soil water level and A2B2 treatment with average value of 106.33 cm and the lowest one was found on 12 cm soil water level and A2B1 treatment with average value of 70.00 cm, respectively. The highest yield was found on 8 cm soil water level and A1B2 treatment with weight of 373.488 g. Treatments of 12 cm soil water level and A1B3 as well as A2B3 had produced zero yield. Semi permeable layer of B2 composition was the best water delivery for chilly crops, whereas 8 cm soil water level was the best water height for chilly crops.  Keywords: Soil water level, thickness and composition of sand and clay.